A Study on EFL Higher Education Student’s Ability to Analyze Grammatical Simple-Past and Past-Perfect Tenses - Sitti Halijah; Muhammad Basri Dalle; Oky Cahyo Sakti Nugroho (Fakultas Sastra - Universitas Muslim Indonesia, 2019)
This study attempts to determine the students` Ability to Analyze the Simple Past and Past Perfect Tenses. The authors used the descriptive method in this study. The population of the research were the fifth semester students of Faculty of Literature UMI Makassar in academic year 2018/2019. The sample of the study consisted of 20 students and were chosen through random sampling method. The istruments used were two kinds of instrument namely objective test and questionnaire to acquire data on their analytical capability of the simple past and past perfect tenses. Findings revealed that the ability of the fifth semester students was deemed as fair. This depicts that the students` ability to analyze Simple Past and Past Perfect Tenses is 59, 20 which was condidered as fair. The problems found faced by the students ability to Analyze the Simple Past and Past Perfect Tenses were; (1) sometimes students were confused in analyzing simple past and past perfect tenses due to the lack of basic knowledge, (2) there were many students who did not have rich vocabularies after they graduated from high school, (3) they had forgotten the pattern of the tenses, and (4) students were still having difficulties to differentiate between simple past and past perfect tenses. The implication of this study is that fresh graduates of senior high school are still lacking the necessary requirements to fullfil the standard English language competency which leads to poor language outcome of the Indonesian high schools today. Hence, the study srongly suggests that it is essential to pay special attention on senior high school students’ second language acquisition before continuing their study in Higher Education.